Peculiar property of noble gases and its explanation through the Enskog--Vlasov model - Benilov, E. S. (2022)
An observation is presented that the ratio of the critical and triple-point temperatures Tcr/Ttp of neon, argon, krypton, and xenon fit within a narrow interval, Tcr/Ttp = 1.803 ± 0.5%, and the same applies to the density ratio, ncr/ntp = 0.3782 ± 1.7% (of the two remaining noble gases, helium does not have a triple point and, for radon, ntp is unknown). We explain this peculiar property by the fact that the molecules of noble gases are nearly spherical, as a result of which they satisfy the Enskog-Vlasov (EV) kinetic model based on the approximation of hard spheres. The EV model has also allowed us to identify two more parameter combinations which are virtually the same for all noble gases.